Effect of Drought and Salt Stress on Cereal Crop Plants and their Proteomic and Physiological Studies - Kaligotla, Venkata Subrahmanya Anirudh; Tanushree, Chakraborty; Rajesh, K. Srivastava; Nasim, Akhtar (Journal of Biotechnology and Biomedical Science, 2020)
The photosynthetic potential and underlying internal metabolism of a plant are some of the most commonly affected physiological functions as a direct consequence of stresses due to salt and water resulting in hindering plant growth and productivity. Under the influence of such detrimental stresses, a drastic alteration in a plant's osmotic requirements, hormonal production, shedding of leaves, and closure of stomata, along with a lessening in the diffusion and transportation of CO2 and H2O are commonly seen. This review unfolds with a description of the basic methodology involved in the proteomic analysis of various proteins involved in stress response along with a brief idea on identifying and obtaining a genomic sequence for proteomic studies. It then dives deep into understanding the impact of abiotic stresses such as salinity, drought and high temperatures on cereal crops such as rice and sorghum as well as the internal dynamics of tolerance mechanism unfolding during stresses have also been described. Extensive literature describing the proteomic and physiological responses to primary and secondary effects of salt stress in cereal crops emphasizing on ROS production and apoptosis, the role of osmolytes as ROS scavengers during osmotic stress and vacuolar antiporters in ionic stress along with the responses during drought stress such as the accumulation of LEA proteins and ABA-based signaling has been reviewed and critically discussed. The study also sheds light on some experimental proteomic studies conducted on the seedlings, root tissues, and shoots of rice cultivars.
Keywords: Abiotic stress; Cereal crops; Drought stress; Plants; Proteomics; Salinity stress.